ANALYSIS OF THE USE OF AUDIO-VISUAL MEDIA IN ARABIC LANGUAGE LEARNING AMONG TENTH GRADE STUDENTS AT MADRASAH ALIYAH NEGERI 1 MEDAN, NORTH SUMATRA - Nasution, Alwi Asnawi; Lubis, Zulfahmi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The use of audio-visual media in Arabic learning in MAN 1 Medan, especially class X, faces challenges such as limited teachers' ability to use it and diverse student responses. Although it has the potential to increase student motivation and understanding, its effectiveness is not optimal. An in-depth analysis is needed to identify the forms of use, advantages, disadvantages, and impacts, as well as provide more effective development recommendations. The method used is qualitative descriptive with data collection through observation, interviews, and documentation. Data were analyzed using Miles and Huberman techniques, including reduction, presentation, and drawing conclusions. Triangulation is carried out to ensure the validity of the data. The results of this study are the use of audio-visual media in Arabic language learning in class X MAN 1 Medan including videos, presentation slides, and audio recordings. This media improves students' motivation, vocabulary comprehension, pronunciation, and sentence structure. However, the limitations of technology and the variation in students' focus are obstacles. As a Conclusion, audio-visual media is effective in improving the quality of Arabic language learning, although challenges such as device limitations and direct interaction still exist. It is recommended that teachers be more innovative, supported by adequate technological facilities, and the use of this media is balanced with other methods for optimal results.